Canada's Ukrainians : negotiating an identity - Hryniuk, Stella M., 1939-; Luciuk, Lubomyr Y., 1953-; Ukrainian Canadian Centennial Committee (Toronto, Ont. : Published in association with the Ukrainian Canadian Centennial Committee by University of Toronto Press, 1991)
The first Ukrainian settlers came to Canada over one hundred years ago. Today the Ukrainian-Canadian community holds a distinct place in the cultural mosaic. This collection of essays, first published in 1991, presents an overview of the community's experience, and brings together the works of over twenty scholars in history, politics, and sociology. Divided into three sections, the first group of essays focus on demography and settlement, the second on relations between the community and the state, while the third considers dynamics within the Ukrainian Canadian community. Archival photographs create a strong sense of time and place.
Without Just Cause: Canada's First National Internment OperationsBritish-Canadian Intellectuals, Ukrainian Immigrants, and Canadian National Identity -- Tracy Philipps and the Achievement of Ukrainian-Canadian Unity -- Ukrainian-Canadian Politics -- Looking for the Ukrainian Vote -- Still Coming to Terms: Ukrainians, Jews, and the Deschenes Commission -- Notes -- Notes on Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Ukrainians -- Canada -- History; Ukrainians -- Canada -- Ethnic identity; Ukrainian Canadians -- History; Ukrainiens -- Canada -- Histoire; Canadiens d'origine ukrainienne -- Histoire; HISTORY -- Canada -- General; Ukrainians; Ukrainians -- Ethnic identity; Canada; Electronic books; e-books.; History; Livres numériques.